Amélioration et conservation du lben le JUNIPERUS COMMUNIS - Bencharef, Djenet; Ferhaoui, Souhila (My University, 2025)
This work aims to develop an improved fermented milk by adding a extracted from juniper powder (Juniperus communis), using an artisanal production method. In this context, we conducted physico-chemical and microbiological analyses on the raw milk in order to assess its sanitary quality and nutritional value before processing . The results showed that it meets Algerian regulatory standards. And for Both traditional lben and the flavored lben were subjected to the same analyses, repeated during the storage period on days 7, 14, 21, and 30, to monitor the evolution of their characteristics and to evaluate the effect of juniper on product stability. A sensory evaluation was carried out with 25 tasters of different ages. The results showed good acceptance of the flavored lben, indicating the possibility of enhancing traditional lben by incorporating natural ingredients with technological and sensory benefits. It was observed that the addition of juniper improves the shelf life of lben, reduces microbial load, and enhances its sensory qualities while preserving its traditional properties.
Keywords: fermented milk; Juniperus communis; juniper; microbiological analysis; shelf life; sensory analysis